ESPÉCIES VEGETAIS NO TRATAMENTO DE ÚLCERAS DIABÉTICAS: Mapeamento de evidências pré-clínicas e levantamento etnobotânico - CHAVES, Rodson Glauber Ribeiro (2025)
Diabetes Mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia, with diabetic foot being one of its most serious complications. This condition results from peripheral neuropathy and occlusive arterial disease, frequently progressing to ulcerations and infections. Despite the available conventional treatments, many patients seek therapeutic alternatives using plants for medicinal purposes. Ethnopharmacological studies are important tools for identifying plant species with therapeutic potential, as well as evaluating risks associated with their use. This thesis is divided into two chapters. Chapter 1 presents the results of an integrative review of in vivo studies of plants for wound healing in hyperglycemic models. After applying exclusion and inclusion criteria, 142 articles were selected, but only 51 were able to answer the proposed guiding question and were included in the research. Several species improved the wound healing process in the studied models. In Chapter 2, an ethnobotanical survey was conducted in public and private health services in the city of Imperatriz in Maranhão. The study's objective was to conduct an ethnobotanical survey of plant species used by patients for treating diabetic foot lesions in health services in Imperatriz-MA, Brazil, located in the Legal Amazon region. Regarding methods, this is an ethnopharmacological study conducted with 103 diabetic patients treated at the Diabetic Foot Outpatient Clinic of the Municipal Hospital of Imperatriz and in a private clinic, from November 2023 to May 2024. Data were collected through interviews using a semi-structured questionnaire, evaluating socioeconomic aspects and the use of plants for medicinal purposes. Ethnobotanical indices were applied, such as Relative Frequency of Citation (RFC), Importance Value (IVS), Use Consensus Value (UCS), and Relative Importance (IR%). Species were classified according to origin and phytogeographic domain and by similarity. Descriptive statistical analyses and Chisquare tests were performed with 5% significance. Regarding results, it was observed that of the 103 participants, 63.1% were male, 33% were aged ≥70 years, 35% had 4-7 years of schooling, and 60.2% had income below two minimum wages. Of the total, 86.4% used medicinal plants and 56.3% specifically for diabetic foot lesions. Thirty-seven plant species were identified, notably Aloe vera (L.) Burm.f. (Aloe), Copaifera langsdorffii Desf. var. langsdorffii (Copaiba), Stachytarpheta cayennensis (Rich.) Vahl (Gervão), Dysphania ambrosioides (L.) Mosyakin & Clemants (Mastruz), and Momordica charantia L. (bitter melon), which showed the highest indices of importance, consensus, and frequency of citation. The leaf was the most used pharmacogene, topical route was the predominant form of administration, and poultice was the most commonly reported method of preparation. Significant adverse effects were reported, including worsening of lesions, digital necrosis, hypoglycemia, and drowsiness. There was no statistically significant association between plant use and the analyzed sociodemographic variables. The study demonstrated widespread use of medicinal plants in the treatment of diabetic foot in the studied population. The occurrence of adverse effects reinforces that traditional use does not guarantee therapeutic safety. It is essential to develop clinical research that validates the efficacy and safety of these species, in addition to implementing educational programs on the rational use of medicinal plants and training of health professionals.